2017
DOI: 10.1080/01902148.2017.1368739
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evidence for the scaffolding effect of alveolar blood vessels

Abstract: A contribution of pulmonary blood distension to alveolar opening was first proposed more than 100 years ago. To investigate the contribution of blood distension to lung mechanics, we studied control mice (normal perfusion), mice after exsanguination (absent perfusion) and mice after varying degrees of parenchymal resection (supra-normal perfusion). On inflation, mean tracheal pressures were higher in the bloodless mouse (4.0α2.5 cmH2O); however, there was minimal difference between conditions on deflation (0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In mice at the embryonic stage (8.5-13 days of gestation), vascular corrosion casting has been applied to investigate embryonic aortic development 8587 and the fetal circulation in relation to the placenta 88,89 . In adult mice, vascular corrosion casting techniques are widely used in all major organs, shown for example to be particularly useful to study cochlear vasculature in age-related hearing loss 9093 , the microvasculature in the urine bladder 94 , and to investigate alveolar anatomy during both physiological development 95,96 and in several diseases 97,98 .…”
Section: Introductionmentioning
confidence: 99%
“…In mice at the embryonic stage (8.5-13 days of gestation), vascular corrosion casting has been applied to investigate embryonic aortic development 8587 and the fetal circulation in relation to the placenta 88,89 . In adult mice, vascular corrosion casting techniques are widely used in all major organs, shown for example to be particularly useful to study cochlear vasculature in age-related hearing loss 9093 , the microvasculature in the urine bladder 94 , and to investigate alveolar anatomy during both physiological development 95,96 and in several diseases 97,98 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that these mechanical deteriorations were probably caused by a diminished tethering effect of the lung periphery through a reduced filling of the pulmonary capillaries that seemed to be more pronounced in children with hypo-perfused lungs than in those with high Qp. Animal studies with restricted Qp supported this hypothesis [ 34 ]. The beneficial postoperative changes in lung mechanics occurring in the VSD infants were consequences of the reversal of the pulmonary vascular engorgement after surgical repair [ 10 ].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, experimental studies suggested that pulmonary vascularization is involved in maintaining the mechanical and architectural properties of the lung. Gibney et al, observed in animal models a decrease in pulmonary compliance if vascularization is stopped [24]. Thus, the mere maintenance of mechanical ventilation may not be able to counteract this "ischemic" closure of the lung.…”
Section: Discussionmentioning
confidence: 99%